The Composite Effect Is Face-Specific in Young but Not Older Adults - Meinhardt, Günter; Persike, Malte; Meinhardt-Injac, Bozana (Frontiers in Aging Neuroscience, 2016)
In studying holistic face processing across the life-span there are only few attempts to separate face-specific from general aging effects. Here we used the complete design of the composite paradigm (Cheung et al., 2008) with faces and novel non-face control objects (watches) to investigate composite effects in young (18-32 years) and older adults (63-78 years). We included cueing conditions to alert using a narrow or a wide attentional focus when comparing the composite objects, and used brief and relaxed exposure durations for stimulus presentation. Young adults showed large composite effects for faces, but none for watches. In contrast, older adults showed strong composite effects for faces and watches, albeit the effects were larger for faces. Moreover, composite effects for faces were larger for the wide attentional focus in both age groups, while the composite effects for watches of older adults were alike for both cueing conditions. Older adults showed low accuracy at the same levels for both types of stimuli when attended and non-attended halves were incongruent. Increasing presentation times improved performance strongly for congruent but not for incongruent composite objects. These findings suggest that the composite effects of older adults reflect substantial decline in the ability to control irrelevant stimuli, which takes effect both in non-face objects and in faces. In young adults, highly efficient attentional control mostly precludes interference of irrelevant features in novel objects, thus their composite effects reflect holistic integration specific for faces or objects of expertise.